A emergência de um sistema dualista: trânsitos e autonomias - Maurílio Antonio Dias (Estudos de Literatura Brasileira Contemporânea)
The aim of this paper is to examine some practices in the editorial market of cordel in the twentieth century. So, we try to show the order that regulated the various agents at work in this system, as well as their relationship of dependency and interest. We verified the high degree of concentration of editorial activities around the character of the poet-editor who, occupying a central position in the universe of such productive relations, achieves a considerable amount of power of interference in the many steps of editing and publishing the cordel.